An Efficient Call Admission Control Algorithm For CDMA Communication Systems - Chan, Mun Leong (2005)
In this thesis, a new call admission control (CAC) algorithm has been devised to achieve better radio resource management (RRM) and utilisation in a UMTS network that employs wideband CDMA (WCDMA) as the air intercafe. This thesis examines some new challenges in radio resource control (RRC) and management of wireless cellular networks that arise from the gradual shifting of their air interface from FDMA and TDMA to CDMA technology.